Dismiss Notice
Join Physics Forums Today!
The friendliest, high quality science and math community on the planet! Everyone who loves science is here!

Proof by Induction Problem

  1. Oct 15, 2011 #1
    1. The problem statement, all variables and given/known data

    So we have to prove that [itex]\frac{(n+1)(n+2)(n+3)...(2n)}{1*3*5...*(2n-1)}[/itex] = 2n

    2. The attempt at a solution

    I. For n=1, obviously the proposition is true. (2*1/(2-1) = 2^1 = 2)

    II. Let n=k and assume [itex]\frac{(k+1)(k+2)(k+3)...(2k)}{1*3*5...*(2k-1)}[/itex] = 2k.

    Now, for n=k+1 we have: 2k * [itex]\frac{(2k +2)}{2k+1)}[/itex] = 2k+1 → 2(k+1)*[itex]\frac{(k+1)}{2k+1)}[/itex] = 2k+1. Which is not true.

    So, I cannot figure out what am I doing wrong.
    Thanks in advance...
  2. jcsd
  3. Oct 15, 2011 #2
    You forgot that in the nominator, you're starting at n+1. So, by doing the transition k->k+1, you need to devide by k+1 also to take that into account. Also, you need to multiply by (2k+1)*(2k+2), since in the nominator you have the product over all numbers between k+1 and 2k.
    So, what you get is: (2k+1)*(2k+2)/(k+1)/(2k+1)=2
Share this great discussion with others via Reddit, Google+, Twitter, or Facebook